КМОП ИС задающего генератора с кварцевой стабилизацией частоты - Zolotarevsky, V. I.; Samotovka, L. I.; Mazaletsky, Yu. D.; Balai, B. A.; Tovmach, E. S.; Voshchinkin, A. F. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper presents the block diagram and functional diagram of the developed CMOS IC, as well as the electrical circuit of the oscillator itself. A calculation method for the oscillator is provided to establish symmetry of its operating point and achieve high sensitivity to input voltage variations in generation mode. The required symmetry of output signal pulses is ensured. The CMOS IC remains operational after exposure to temperatures ranging from –60 °C to +125 °C. The structural characteristics of the IC are comparable to imported samples.